Corporate venture capital: Strategies for success - Sykes, Hollister B. (Journal of Business Venturing, 1990)
Currently, about 80 major companies have venture capital programs that were started for strategic reasons—to help foster new business development. Yet the results have been mixed. Some companies consider their programs successful. Others have doubts. Others have quit. To explore causes for this disparity of results, survey data were gathered from 31 major corporations through questionnaires and followup interviews. Only strategic investment programs, where the motivating purpose is to assist corporate new business development, were covered. Programs conducted solely for financial return were excluded. Data on two modes of venture capital investment were obtained: venture capital investment (VCI) directly in new ventures and investment in venture capital limited partnerships (VCLPs) managed by private venture capital firms. Corporations were asked to rate, on a five-level scale, the overall contribution (added value) of their programs in meeting their strategic objectives. In the survey, eight factors were probed to determine their possible effect on the strategic value rating. Four of these factors appear to have a significant influence on strategic value: choice of primary strategic objective, type and frequency of communications with the ventures or VCLPs, return on portfolio investment and mode of investment (VCI vs. VCLP). Objectives that produce a mutually supportive environment, such as formation of corporate/venture business relationships, are more likely to lead to success. Objectives that induce a potential conflict of interest between the corporations and the venture, such as venture acquisition, may lead to a nonproductive environment and failure of the relationship. Modes of communication that involve direct and frequent contact between the corporation and the venture regarding areas of special or mutual interest produce the highest strategic value. Of questionable value are routine reports and attendance at venture board meetings. Reported return on investment for those programs that had been in operation for five or more years averaged 14 to 15%. Portfolio ROI% was positively related to strategic value in the case of investment in VCLPs, but no significant relationship was found in the case of VCI investments. Comparison of the strategic value of direct vs. VCLP investment showed opinion predominantly in favor of direct investment if only one strategy were chosen. However, as the interviews brought out, the two programs can serve somewhat different purposes and be complementary to one another. The most effective combination is one in which the VCLP investments provide contacts with the venture capital community and “deal flow” and the direct investments enhance specific business relationships such as marketing or research agreements. The implication of these results for corporate investors is that program strategic success can be significantly enhanced by a proactive approach involving frequent interaction with the ventures or venture capital firms regarding specific issues of mutual interest. One of the most effective channels for interaction is through the formation of business relationships (“strategic partnerships” in current parlance). Financial returns will probably be acceptable and additive to any strategic returns.